The Effectiveness of Slow Sand Filtration on Reduction of Iron (Fe) and Calcium (CaCO3) Levels in Water - Moh. Andri; Budiman; Fabotin Taib (Universitas Muhammadiyah Palu, 2023)
Ground water or well water is the largest source of clean water used. The most common obstacle in using groundwater is the problem of iron (Fe) and calcium (CaC03) content in raw water. This research aims to determine the effectiveness of slow sand filtration to reduce Fe and CaCO3 levels in water. This type of research is a pure experimental study in a re-treatment design (One Group Pretest Posttest). The samples of raw water were taken from water pump wells owned by residents on JI. Datu Adam, Lere Village. Sample testing after slow sand filtering was carried out at the UPTD Laboratory of the Office of Environment, Donggala. The filter was carried out with a medium thickness of 45 cm sand, 5 cm gravel sand, 7 cm gravel and 5 cm high puddle water. Before filtering the test results Fe 0.4mg/L and CaCO3 546.37mg/L. Based on the effectiveness test of slow sand filtration with 3 treatments, it was found that the levels of substances after filtering were iron (Fe) 0.29, 0.21 and 0.I2 mg/L respectively, while calcium (CaCO3) was 273.41, 241.35 and 210.11 mg/L respectively. From these results, slow sand filtration is effective in reducing Fe and CaCO3 levels in water. The community is expected to be able to use simple filtering media such as slow sand filters to reduce iron (Fe) and calcium (CaCO3) levels in water. It is also expected to provide additional knowledge studies in the field of public health, especially environmental health.